Epidemiological characteristics and spatiotemporal patterns of typhus group rickettsiosis at the county level in China, 2005–2017. (February 2020) - Gao, Yuan; Yan, Dongming; Liu, Keke; Sun, Jimin; Niu, Yanlin; Liu, Xiaobo; Wu, Haixia; Zhao, Chunchun; Yue, Yujuan; Wang, Jun; Zhao, Ning; Lu, Liang; et al.
Highlights: We first explored the epidemiological characteristics and spatiotemporal clusters of typhus group rickettsiosis in mainland China. The hotspots were located mainly in the southwestern, southern, and circum-Bohai Sea regions of northern China. The primary spatiotemporal cluster showed a trend shifting from circum-Bohai Sea regions to the southwestern regions of mainland China. Abstract: Objective: To explore the epidemiological characteristics and spatiotemporal patterns of typhus group rickettsiosis (TGR) in mainland China. Methods: A chi-squared test was used to compare the differences in the age and occupation distributions across the different years. Time-series analyses, spatial clustering analyses, and spatiotemporal scan statistics were used to detect the spatiotemporal patterns of the TGR incidence. Results: A total of 29, 211 TGR cases were collected. Of these cases, 63.1% occurred from May to October, and 88.4% occurred in individuals between 0 and 59 years old. There was a significant spatial TGR heterogeneity from 2005 to 2017. The hotspots were located mainly in the southwestern, southern, and circum-Bohai Sea regions of northern China. Eighteen spatiotemporal clusters were observed using Kulldorff's space-time scan statistic, and the primary cluster included three counties, Jinghong city, Menghai county, and Mengla county. Conclusions: TGR is widely distributed in China, and it is a serious threat to public health. The hotspots were located mainly in the southwestern, southern, and circum-Bohai Sea regions of northern China, and the primary spatiotemporal cluster showed a trend shifting from circum-Bohai Sea regions to the southwestern regions. Targeted interventions should be executed in high-risk regions for precise prevention and control.